× Cochlezella costaricensis, a Name for a Rare Natural Hybrid in the Zygopetalinae (Orchidaceae) - Pupulin, Franco (2015)
A new nothospecies in the subtribe Zygopetalinae (Orchidaceae), × Cochlezella costaricensis, representing a cross between Cochleanthes aromatica and Warczewiczella discolor, is described and illustrated from Costa Rica, and its relationships are discussed.